Freer markets, more rules regulatory reform in advanced industrial countries - Vogel, Steven Kent (Cornell studies in political economy, 1996)
Over the past fifteen years, the United States, Western Europe, and Japan have transformed the relationship between governments and corporations. The changes are complex and the terms used to describe them often obscure the reality. In Freer Markets, More Rules, Steven K. Vogel dispenses with euphemisms and makes sense of this recent transformation